Theoretical research and development of new design of beet tops harvesting machinery - Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич (My University, 2017)
Beet tops harvesting machines designs working out is actual scientific and technical task for beet industry. Development of beet tops harvesting machine with technical and operational indicators of work on the level of the best world analogs is research objective. In the research used the methods of design and construction of agricultural machinery, methods of creation calculation mathematical models based on higher mathematics, theoretical mechanics, as well as programming and numerical calculations on the PC. Theoretical researches of technological process sugar beet tops cutting by the rotor mechanism are conducted. The mathematical model of interaction beet tops bunch with arc-shaped blade of knife which pivotally mounted on a power horizontal shaft is constructed. New analytical dependence of full cutting beet tops bunch of a given diameter on constructive, kinematic and power parameters of this design of beet tops harvesting machines is obtained. The dependence for speed definition of beet tops cutting device which providing effective cutting of tops bunches from sugar beet root crops which are in the soil is found. Carried out on the PC, numerical calculations, made it possible to determine the design parameters of the new rotary beet tops harvesting device. Tests of the beet tops harvesting machine in different zones of sugar beet cultivation showed that technical and operational indicators of its work correspond to the level of the best world analogs
Keywords: sugar beet; beet tops cutting; rotor; mathematical model; unsupported cutting; design parameters